2010
DOI: 10.1177/0038040710392717
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national Differences in Educational Achievement Inequality

Abstract: School systems are called not only to instruct and socialize students but also to differentiate among them. Although much research has investigated inequalities in educational outcomes associated with students’ family background and other ascriptive traits, little research has examined cross-national differences in the total amount of differentiation that school systems produce, the total achievement inequality. This article evaluates whether two dimensions of educational systems—variations in opportunities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 67 publications
1
60
0
6
Order By: Relevance
“…For instance, in reality, we might not control and change the SES to improve achievement, but we can change the factors that influence the effect of SES on reading performance. As Montt (2010) writes, "by reducing the strength of the relationship between socioeconomic status and achievement in a school system, the overall distribution of achievement is also equalized" (p. 62). Moreover, Willms (2006) recommends that a mix of interventions will be optimal to achieve both excellence and equity because a combination of factors can jointly maximize these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in reality, we might not control and change the SES to improve achievement, but we can change the factors that influence the effect of SES on reading performance. As Montt (2010) writes, "by reducing the strength of the relationship between socioeconomic status and achievement in a school system, the overall distribution of achievement is also equalized" (p. 62). Moreover, Willms (2006) recommends that a mix of interventions will be optimal to achieve both excellence and equity because a combination of factors can jointly maximize these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of family socioeconomic status (SES) was related to student achievement in the FIMS, indicating that the strong effect of family background noted in the contemporaneous Coleman Report (1966) was not restricted to the United States. More recent research has verified the continuing importance of family background to achievement in ILSAs (Baker et al, 2002;Woessman, 2004;Chudgar & Luschei, 2009;Montt, 2011). Methodological debates, particularly with respect to measuring SES, have resulted in varying estimates of SES-based inequality.…”
Section: Cross-country Differences In Within-country Variationmentioning
confidence: 99%
“…Heyneman and Loxley (1983) argue that although school resources do not have a strong effect in wealthier countries, they do mitigate SES gaps in developing countries. Sousa and Armor (2010) also found that school resources could shrink achievement gaps (see also Montt, 2011). However, whether this phenomenon persists -or indeed ever existed -has been called into question using many of the same individual-and school-level ILSA data (Baker et al, 2002;Chudgar & Luschei, 2009;Hanushek & Luque, 2003).…”
Section: Efforts To Mitigate Educational Inequalitymentioning
confidence: 99%
See 2 more Smart Citations